Highly tunable arylated cinchona alkaloids as bifunctional catalysts - CONNON, STEPHEN (My University, 2012)
We report the design and evaluation of a library of chiral bifunctional organocatalysts in which the distance between the catalytically active units can be systematically varied.
PUBLISHED
Keywords: Chemistry